2015
DOI: 10.1007/s12663-015-0840-z
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Orbital Floor Fractures with Porous Polyethylene Implants: A Prospective Study

Abstract: Purpose The main aim of our study was to assess and evaluate the efficacy, long standing outcome and infection of porous polyethylene implants in treatment of orbital floor fractures. Patient and methods Twelve patients with fractures of orbital floor were included in the study. The cause of fracture was road traffic accident, self fall and cow hit respectively. They also complained of enophthalmos (n = 9), diplopia (n = 3), restricted eye movement (n = 2), impairment of infraorbital nerve (n = 3) and dystopia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…Although undeniable progress in the management of orbital floor fractures has occurred over the past decades, there is still a lack of broad consensus as to which material(s) should be used to restore proper anatomy of the orbital floor in order to achieve best clinical results. This is also reflected by the still very high number of recent studies describing various approaches and materials to reconstruct the orbital floor, such as titanium meshes [27], partially absorbable meshes [28], bioresorbable implants [29,30], resorbable collagen membranes [31], polydioxanone foils [32], porous polyethylene sheets [33], bioactive glass S53P4 implants [34], auricular conchal grafts [35], rib bone grafts [36], or heterologous cortical bone [37].…”
Section: Discussionmentioning
confidence: 99%
“…Although undeniable progress in the management of orbital floor fractures has occurred over the past decades, there is still a lack of broad consensus as to which material(s) should be used to restore proper anatomy of the orbital floor in order to achieve best clinical results. This is also reflected by the still very high number of recent studies describing various approaches and materials to reconstruct the orbital floor, such as titanium meshes [27], partially absorbable meshes [28], bioresorbable implants [29,30], resorbable collagen membranes [31], polydioxanone foils [32], porous polyethylene sheets [33], bioactive glass S53P4 implants [34], auricular conchal grafts [35], rib bone grafts [36], or heterologous cortical bone [37].…”
Section: Discussionmentioning
confidence: 99%
“…The use of 3D CAD/CAM to manufacture a custom implant has thus recently become a popularly researched technique [24,25] and studies have shown decreased complication rates and improved accuracy. When applied to a pediatric patient in this study, the same results were found.…”
Section: Discussionmentioning
confidence: 99%
“…High-density porous polyethylene is biocompatible, creating minimal surrounding soft-tissue reaction; has high tensile strength; and is nonresorbable. 72,73 The main disadvantage of high-density porous polyethylene is that it is not easily visible on postoperative computed tomographic scans. Composite implants, made of high-density porous polyethylene with embedded titanium mesh, combine the qualities of both materials and improve radiographic visualization of the implant.…”
Section: Surgerymentioning
confidence: 99%